Drug Reaction with Eosinophilia and Systemic Symptoms: DRESS following Initiation of Oxcarbazepine with Elevated Human Herpesvirus-6 Titer - Seth L. Cornell; Daniel DiBlasi; Navin S. Arora (Hindawi Limited, 2014)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare and potentially fatal severe cutaneous reaction, which has a delayed onset after the initiation of an inciting medication. After recognition and withdrawal of the causative agent, along with aggressive management, a majority of patients will have complete recovery over several months. We present a rare case of DRESS secondary to oxcarbazepine with an elevated human herpesvirus-6 titer.